PENGEMBANGAN MEDIA PEMBELAJARAN INFORMATIKA BERBASIS PENDEKATAN KONTEKSTUAL PADA MATERI BERPIKIR KOMPUTASIONAL - Rohandi, Manda; Rijal, Bait Syaiful; Sahda, Siti Sal (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2024)
The results of observations found several problems, namely, the lack of variation in the use of media in delivering subject matter, this causes student interest in learning computational thinking material is still lacking. The purpose of the study was to develop and assess the feasibility of web-based learning media using Google Sites with a contextual approach and measure student interest in the media. The method used is Research and Development (R&D) with the ADDIE model. with instruments by media experts and material experts, as well as measuring student interest in learning. The research subjects consisted of 32 students of class X-8 at SMA Negeri 1 Kabila. The results showed that (1) learning media obtained a very feasible assessment from media experts with a percentage of 81.25% and from material experts with a percentage of 97.08% (2) Student learning interest in this media was also high with a percentage of 70.24%. It can be concluded that web-based learning media is declared feasible to use for computational thinking material. The research suggestion is for teachers to continue to develop the use of this web-based learning media for various other materials, and for further research to expand the scope of using the media in all classes and subjects, so that it can support independent learning that is fun and motivating for students.